PEMETAAN POTENSI KOMODITAS DAN RANCANGAN PENGEMBANGAN DI KECAMATAN BLEGA, BANGKALAN MADURA - Agus Romadhon; - Sucipto (Universitas Trunojoyo Madura, 2010)
Agriculture in rural areas relate to dense population and the relatively limited resources. Efforts to develop the agricultural sector can be done by knowing the level of productivity of each commodity in each rural region. Therefore the handling of rural areas and agricultural activities have become very strategic. The purpose of this study was to increase agricultural competitiveness and competitive advantages of Blega by developing a number of potential commodity based on the result of potential commodity mapping. The methodology used in this research are: 1. Field survey, 2. Observation (observation), 3. Secondary data studies, 4. Transect. The results of potential commodity identification in the Blega district are food crops (rice, field rice, corn, peanut, cassava, chilli. guava, water guava, sapodilla, banana, mango, jackfruit and durian) and plantations crop (coconut, cotton, cashew and long pepper).